2003
DOI: 10.1097/01.meg.0000059158.46867.a6
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of liver function by the methionine and aminopyrine breath tests in the early stages of liver transplantation

Abstract: Objective The early phase after liver transplant is considered the period of greatest risk for graft failure. In recent years breath tests have been proposed as a noninvasive method to assess liver function. In particular, the aminopyrine breath test is useful for evaluating the liver viable mass, and the methionine breath test could be used to evaluate oxidative capacity of liver mitochondria. We aimed to perform these tests in the early phase following liver transplant in order to correlate the time course o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
2
5
0
2
Order By: Relevance
“…We agree with the authors that 13 C breath testing may be useful for monitoring hepatic function in patients waiting for orthotopic liver transplantation and during follow‐up after this procedure, as described in a recent paper 2 . In particular, we have shown that 13 C‐aminopyrine and 13 C‐methionine breath tests are useful in the early phases after orthotopic liver transplantation to predict primary non‐function of the transplanted liver 2 . However, we prefer to use the 13 C‐aminopyrine breath test for the investigation of liver function in end‐stage cirrhotic patients, which, in our opinion, is more reliable than the 13 C‐methionine breath test.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…We agree with the authors that 13 C breath testing may be useful for monitoring hepatic function in patients waiting for orthotopic liver transplantation and during follow‐up after this procedure, as described in a recent paper 2 . In particular, we have shown that 13 C‐aminopyrine and 13 C‐methionine breath tests are useful in the early phases after orthotopic liver transplantation to predict primary non‐function of the transplanted liver 2 . However, we prefer to use the 13 C‐aminopyrine breath test for the investigation of liver function in end‐stage cirrhotic patients, which, in our opinion, is more reliable than the 13 C‐methionine breath test.…”
supporting
confidence: 85%
“…in a recent issue of Alimentary Pharmacology and Therapeutics 1 . We agree with the authors that 13 C breath testing may be useful for monitoring hepatic function in patients waiting for orthotopic liver transplantation and during follow‐up after this procedure, as described in a recent paper 2 . In particular, we have shown that 13 C‐aminopyrine and 13 C‐methionine breath tests are useful in the early phases after orthotopic liver transplantation to predict primary non‐function of the transplanted liver 2 .…”
supporting
confidence: 64%
“…Über die oben genannten Substrate hinaus wurden 13 C-Phenylalanin [222, 236 -239], 13 C-Methionin [233,240,240,241], 13 C-Koffein [242], 13 C-Galaktose [243] und 13 C-Oktansäure [244] zur Messung der hepatischen Funktion eingesetzt. Mit den entsprechenden Atemtests lässt sich in der Regel eine sichere Diffe-renzierung zwischen Patienten mit einer chronischen Lebererkrankung und Gesunden [222,234,236] bzw.…”
Section: Erläuterungenunclassified
“…The enteral version of the MBT has been shown to correlate with both hepatic steatosis and cirrhosis in adults (27). Similarly, adult liver transplant outcomes (28) and HIV patient drug-induced hepatic toxicity (18) have been predicted by an orally administered [ 13 C]-MBT. Furthermore, in HIV-infected adults, oral [ 13 C]-MBT results were shown to be an earlier marker of hepatic mitochondrial dysfunction than either standard liver function tests or patient symptomatology (29).…”
Section: Discussionmentioning
confidence: 99%